Assessment and treatment of sexual offenders with intellectual disabilities a handbook - Craig, Leam; Lindsay, William R.; Browne, Kevin D. (Kevin Dominic) (Wiley series in forensic clinical psychology, 2010)
A practical handbook for practitioners that covers the assessment, treatment and management of sexual offenders with intellectual disabilities - an area of growing interest within clinical forensic psychology.: New for the Wiley Series in Forensic Clinical Psychology: a practical handbook that covers the assessment, treatment and management of sexual offenders with intellectual disabilities; Summarises the research literature on the characteristics and prevalence of sexual offenders with intellectual disabilities; Discusses risk assessment and innovations in treatment and management; Includes.